THE ENHANCEMENT OF IDENTIFYING CONCLUSIONS SKILL IN REACTION RATE CONCEPT BY PREDICT-OBSERVE- EXPLAIN LEARNING MODEL - ni wayan eviyanti; Noor Fadiawati; chansyanah diawati (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
The aim of this research is to describe the effectiveness of POE learning model in reaction rate concept to enhance identifying conclusion skill.  Students who became the subject of this research was  XI grade of Science 1 Bandar Lampung Senior High School in Bandar Lampung Academic Year 2012/2013.  This research used the pre-experimental method and one group pretest-posttest design. The effectiveness of POE  learning model was determined based on the average value of n-Gain.  The results of this research showed that the average value of n-Gain of identifying conclusion skill was 0,65.  Thus, it can be concluded that the POE learning model in reaction rate concept effective to enhance identifying conclusion skill in medium category. Keywords: POE learning and identifying conclusions skill